Conference Review: ICA II Conference Paris, France - E. Giovanna Fregni (EXARC, 2020)
The ICAII International Conference on Archaeometallurgy was held 25 September to 1 October 2019 at the Sorbonne University, Paris-Saclay University, and at Melle dans le Poitou where experiments were conducted. Papers were delivered in French and English and primarily focused on the metallurgy of the Bronze Age and New Kingdom periods in Egypt and the Middle East, using evidence from excavated materials and depictions of metalworking in art.